Cantilever arrayed blood pressure sensor for arterial applanation tonometry - Lee, Byeungleul; Jeong, Jinwoo; Kim, Jinseok; Kim, Bonghwan; Chun, Kukjin (INST ENGINEERING TECHNOLOGY-IET, 2014)
The authors developed a cantilever-arrayed blood pressure sensor array fabricated by (111) silicon bulk-micromachining for the non-invasive and continuous measurement of blood pressure. The blood pressure sensor measures the blood pressure based on the change in the resistance of the piezoresistor on a 5-m-thick-arrayed perforated membrane and 20-m-thick metal pads. The length and the width of the unit membrane are 210 and 310 m, respectively. The width of the insensible zone between the adjacent units is only 10 m. The resistance change over contact force was measured to verify the performance. The good linearity of the result confirmed that the polydimethylsiloxane package transfers the forces appropriately. The measured sensitivity was about 4.5%/N. The maximum measurement range and the resolution of the fabricated blood pressure sensor were greater than 900 mmHg ( = 120 kPa) and less than 1 mmHg ( = 133.3 Pa), respectively.
Keywords: VARIABILITY; FABRICATION